Determinants of life satisfaction of working women: a study in balangoda divisional secretariat division - Himali, L.P.; Wijesekara, N.M. (University of Jaffna, 2016)
In this era, every country in the world demonstrates a great interest to know the social and economic position of women, because the role of the women has been expanded throughout the past. Though much progress has been made in the society to bring women to a stage, still it is not fully achieved. In most of the cases, women have to spend their entire lives with less pleasure or unhappy, stress and tension and this will lead to decrease women's life satisfaction and it is inversely affected to the development and stability of any economy. The purpose of this study is to identify the determinants of life satisfaction of working women. The study used primary data and 142 women were selected from 3 GN Divisions in Balangoda DS Division which represent urban, rural and estate sector through cluster sampling and convenience sampling methods. The data was collected using an already developed structured questionnaire. Binary Logistic Regression models were used as main analyzing technique. Results revealed that nature of the job, attitudinal concern on social validity for the job, access for leaves and education level emerged as significant predictors of life satisfaction of working women. Education level has importantly influenced the life satisfaction of working women and all above factors have positive relationship with life satisfaction.
Keywords: Determinants; Life satisfaction; Working women